Façade Complexity as a Construction Cost Driver in Small Dwellings - Suwardi Tedja; Carissa Carissa (RekaRacana: Jurnal Teknik Sipil, 2026)
ABSTRACTThis study examines how architectural façade articulation influences construction cost efficiency in small dwellings. While construction economics typically emphasises materials and structural systems, architectural design complexity remains weakly quantified using empirical cost data. The paper develops and tests a Façade Complexity Index (FCI) that translates observable façade articulation into measurable variables associated with construction cost performance. A comparative exploratory case study was conducted on five affordable housing prototypes with identical floor areas (22 m²), construction year, and structural systems. Actual Bills of Quantities (BoQ) were converted into constant prices using the Indonesian Construction Cost Index (IHPB, BPS 2008–2026) and normalised into cost per square metre. The analysis applied cost benchmarking, cost structure decomposition, exploratory Spearman correlation, and sensitivity analysis. Construction cost intensity varied by more than 30% across cases despite identical size and structural systems. Finishing works accounted for 44–55% of the total cost. A positive association (ρ ≈ 0.70) was observed between FCI scores and cost per square metre. Simplifying façade articulation and roof complexity could reduce total cost by approximately 10–15% without affecting housing function. The study is exploratory and limited to five cases within one regional context, restricting generalisability. The FCI provides a practical early-stage design-to-cost evaluation tool for managing finishing complexity and affordability targets.Keyword: design-to-cost, construction economics, architectural design complexity, façade complexity index, cost structure decomposition, value engineering